Lobengula of Zimbabwe - Bhebe, Ngwabi (Heinemann Educational Books Ltd, 1977)
Lobengula,despite considerable personal gifts,was never sufficiently autocratic to enable his people to resist Rhodes.
Keywords: Juvenile literature-Biographies-History-Zimbabwe-Nonfiction